Knowledge, attitude and practice of caregivers on medication management at residential aged care facilities in Malaysia - Mariani AN; Marhanis Salihah Omar; Adliah Mhd Ali; Mohd MB (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
An escalating proportion of the aged group is associated with a growth in the prevalence of ill health. With the complexity of age-related diseases, a good medication management system is important to prevent medication errors. This study was aimed to develop a questionnaire to assess the knowledge, attitude and practice (KAP) of caregivers on medication management at residential aged care facilities (RACFs). A cross-sectional study was performed involving caregivers from 90 RACFs throughout Malaysia. The validated self-administered questionnaire was developed based on the extensive literature review and expert`s opinions containing 41-items divided into three domains. In this study, the response rate was 71% with 128 questionnaires returned. Median scores obtained for knowledge, attitude and practice were 77.27, 70.83 and 68.66, respectively. Majority of the caregivers (71.9%) deemed to know what medication management was. However, nearly half of them (48.4%) did not experience any training. More than half of the caregivers possessed good level of knowledge (69.5%, n = 89), around half (57.8%, n= 74) had a good attitude and less than half had a good practice (46.9%, n= 60) of medication management. Level of education, special qualification and experience of medication management training were the factors that correlated with good score outcome (p<0.05). Therefore, it is assumed that more support and training can be provided to the caregivers in RACF on medication management.